Der Zusammenhang zwischen technischer Effizienz und wirtschaftlichem Erfolg: eine Analyse für bayerische Milchviehbetriebe; The Relationship between Technical Efficiency and Economic Success: The Case of Bavarian Dairy Farms - Magnus Kellermann; Klaus Salhofer; Wolfgang Wintzer; Christian Stockinger (German Journal of Agricultural Economics (GJAE), 2011)
– The objective of this article is to reveal the relationship between technical efficiency and the economic success of dairy farms and to determine farm specific factors affecting both. The data set contains observations of more than 2 000 Bavarian dairy farms in an unbalanced panel covering the years 2000 to 2008. We use the stochastic frontier approach to analyze the technical efficiency of farms. Economic success is measured by the performance indicator "Nettorentabilitaẗ", which is the rate of return on farm owned production factors. Findings show an average technical efficiency of 88,2 % and an average "Nettorentabilitaẗ" of approximately 57 %. A rank correlation test indicates a strong positive relationship between technical efficiency and economic success. We calculate the marginal effects of possible determinants of technical efficiency and economic success and reveal that both improve with farm mangers education level, full-time farming and soil quality.
Keywords: 330